Kedudukan notaris sebagai turut tergugat dalam perkara perdata - I Gusti Ngurah Adnyana (Jurnal Cakrawala Hukum, 2022)
The filing of a lawsuit to the court must meet the formal requirements of the lawsuit, including the plaintiff and the defendant must be complete based on a legal relationship and based on the fact that the party in control or the party claiming to have a right to an object must also be sued. The incompleteness of the parties in a lawsuit can cause the lawsuit to be declared lacking parties so that the lawsuit can be declared unacceptable. However, for a lawsuit based on a deed made before a notary where the position of the notary in a lawsuit is very dependent on the arguments of the lawsuit filed by the plaintiff. The problem to be raised is whether the notary has a legal relationship with the parties who made the deed, or does the notary have a legal obligation to be responsible if one of the parties making the deed suffers a loss? This writing uses a normative method. The results and discussion show that the position of the notary as a party to a lawsuit based on the deed he made must pay attention to the basis or argument of the lawsuit such as default, or cancellation due to false information, or acts against the law. Thus, it can be said that a lawsuit based on a deed made by a notary where the notary is not included as a co-defendant does not necessarily mean that the plaintiff's claim can be declared lacking parties so that the lawsuit is NO.